Ex Vivo Evaluation of the ArtVentive EOS Occlusion Device for the Management of Biliary Leaks - Kuetting, Daniel; Schild, Hans Heinz; Pieper, Claus Christian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose Percutaneous treatment of biliary leaks is frequently required, yet technically challenging and limited to smaller fistulas. This study sought to evaluate the off-the-shelf use of the ArtVentive EOS device for the occlusion of biliary or cystic stump leaks.Materials and Methods ePTFE-covered ArtVentive EOS devices were used to perform biliary leak embolization in 5 explanted porcine livers and in 3 explanted bovine livers. After establishing standard percutaneous transhepatic biliary drainage access, artificially created biliary leaks were occluded using 5 & 8 mm EOS devices. Using the 5 mm device, peripheral (n = 3), central (n = 1) and cystic duct leaks (n = 1) were occluded. Using the 8 mm device, peripheral (n = 1), central (n = 1), main (n = 1) and cystic duct leaks (n = 2) were occluded. Total leak occlusion was controlled by cholangiography.Results Selective deployment and occlusion of central biliary leaks (3/3) and cystic stump leaks (3/3) was successful in all cases. Peripheral leaks could not be selectively catheterized in 3 out of 4 cases, making device deployment several millimeters proximal to the leaks necessary.Conclusion Selective occlusion of the cystic stump, central biliary, and larger peripheral biliary leaks using the EOS device is technically feasible ex-vivo in a single setting.Key points Citation Format
Keywords: biliary leaks; percutaneous embolization; occlusive device; EOS